Interplay Among Hydrogen Sulfide, Nitric Oxide, Reactive Oxygen Species, and Mitochondrial DNA Oxidative Damage - Huang, Dandan; Jing, Guangqin; Zhang, Lili; Chen, Changbao; Zhu, Shuhua (Frontiers in Plant Science, 2021)
Hydrogen sulfide (H2S), nitric oxide (NO), and reactive oxygen species (ROS) play essential signaling roles in cells by oxidative posttranslational modification within suitable ranges of concentration. All of them contribute to the balance of redox and involve in the DNA damage and repair pathways. However, the damage and repair pathways of mitochondrial DNA (mtDNA) are complicated, and the interactions among NO, H2S, ROS, and mtDNA damage are also intricate. This paper summarized the current knowledge about the metabolism of H2S, NO, ROS and their roles in maintaining redox balance and regulating the repair pathway of mtDNA damage in plants. The three reactive species may likely influence each other in their generation, elimination, and signaling action, indicating a crosstalk relationship between them. What is more, NO and H2S are reported to be involved in epigenetic variations by participating in various metabolisms of cells, including (nuclear and mitochondrial) DNA damage and repair. Nevertheless, the research on the details of NO and H2S in regulating DNA damage repair of plants is in its infancy, especially in mtDNA.